Non-enzymatic antioxidant capacity and risk of gastric cancer. Issue 3 (June 2015) - Praud, Delphine; Parpinel, Maria; Serafini, Mauro; Bellocco, Rino; Tavani, Alessandra; Lagiou, Pagona; La Vecchia, Carlo; Rossi, Marta
Highlights: Relation between non-enzymatic antioxidant capacity and gastric cancer was examined. We used three different dietary measures of non-enzymatic antioxidant capacity. A protective role of high levels of antioxidant capacity on gastric cancer was found. This could explain the relation between fruit and vegetable intake and gastric cancer. Abstract: Background: Consumption of fruit and vegetables has been inversely related to gastric cancer. Two studies found that dietary antioxidant capacity has some role in explaining this association. We investigated the overall antioxidant effect from diet on gastric cancer using three measures of non-enzymatic antioxidant capacity (NEAC). Methods: We used data from an Italian case-control study including 230 patients with incident, histologically confirmed gastric cancer, and 547 frequency matched controls admitted to the same hospitals for acute non-neoplastic diseases. A reproducible and valid food frequency questionnaire was used to assess subjects' usual diet. NEAC was measured using Italian food composition tables in terms of Trolox equivalent antioxidant capacity (TEAC), Ferric reducing-antioxidant power (FRAP) and Total radical-trapping antioxidant parameter (TRAP). We estimated the odds ratios (OR) of gastric cancer and the corresponding 95% confidence intervals (CI) using conditional logistic regression models including terms for recognized gastric cancer risk factors and total energy intake. Results: NEAC was inversely related with gastric cancer risk with ORs for the highest versus the lowest quintile of 0.54 (95%CI, 0.33–0.88) for TEAC, 0.67 (95%CI, 0.42–1.07) for FRAP and 0.57 (95%CI, 0.36–0.90) for TRAP. Conclusions: A diet rich in antioxidant capacity reduced gastric cancer risk, suggesting a high consumption of fruit and vegetables and a moderate consumption of wine and whole cereals.